ANALISIS PENDEKATAN TARL DALAM MODEL PEMBELAJARAN PJBL PADA MATA PELAJARAN IPA - Nurlaili Rosyidah; Indriati Nurul Hidayah; Nurlaili Rosyidah (Universitas Negeri Malang, 2024)
In the subject of Natural Sciences, PjBL offers the ability to enhance students' understanding of concepts and scientific skills through practical exploration activities. However, in its implementation, the PjBL model also faces several challenges. Some of these include difficulties in integrating a dense curriculum with project-based learning approaches, resource limitations, and challenges in assessing students' achievements comprehensively. In an effort to address these challenges, an innovative learning approach emerged, namely Teaching at the Right Level (TaRL). The aim of this research is to analyze the TaRL approach within the PjBL model in the science subject, focusing on how the combination of these two methodologies can enhance student engagement and motivation. This research method employs descriptive research using a qualitative approach. Data collection techniques in this study include observation and documentation. The research instruments used in this study include observation and document analysis. The results of applying this approach have been proven to increase student engagement in learning, as it provides opportunities for them to learn independently and collaborate on challenging projects. Although it has not fully enhanced students' intrinsic motivation towards learning science.